Oxidative stress and Cx43-mediated apoptosis are involved in PFOS-induced nephrotoxicity. (August 2022) - Tang, Leilei; Yu, Jiawen; Zhuge, Sheng; Chen, Hangping; Zhang, Lingdi; Jiang, Guojun
Abstract: Perfluorooctane sulfonate (PFOS) is a persistent organic pollutant that can cause nephrotoxicity. However, the underlying mechanisms are not fully understood and require further investigation. In the present study, we established a PFOS-exposed Sprague-Dawley (SD) rat kidney injury model by intraperitoneal injection of PFOS (1 mg/kg and 10 mg/kg body weight) every alternate day for 15 days and cytotoxicity models of normal rat kidney epithelial (NRK52E) and human renal proximal tubular (HK2) cells exposed to PFOS (20 μM and 60 μM) for 24 h to reveal the mechanisms underlying PFOS-induced nephrotoxicity. Data showed that PFOS increased the kidney index and induced nephrotoxicity in rats. Furthermore, PFOS significantly increased malondialdehyde (MDA) levels, decreased GSH peroxidase (GSH-PX) activity in kidney tissues, and increased intracellular reactive oxygen species (ROS) levels in NRK52E and HK2 cells. Following PFOS treatment, mitochondrial damage in the renal tubular epithelial cells of rats was observed and the mitochondrial membrane potential (ΔΨm) was decreased in NRK52E cells. PFOS upregulated apoptosis of tubular epithelial cells and expression of Connexin 43 (Cx43) in vitro and in vivo . The Cx43 inhibitor gap26 attenuated the apoptosis of tubular epithelial cells. In conclusion, our findings reveal that PFOS may trigger renal tubular cell apoptosis through oxidative stress and upregulation of Cx43, resulting in PFOS-induced nephrotoxicity.